The Safety of Intralesional Steroid Injections in Young Children and Their Effectiveness in Anastomotic Esophageal Strictures—A Meta-Analysis and Systematic Review - van Hal, Annefleur R. L.; Pulvirenti, Rebecca; den Hartog, Floris P. J.; Vlot, John (Frontiers in Pediatrics, 2022)
Objective Intralesional steroid injections (ISI) are a widely used technique for various pediatric indications and represent a possible adjuvant treatment for anastomotic esophageal strictures. Yet, no consensus has been reached neither on their safety in the pediatric population or their effectiveness in esophageal atresia patients. This systematic review aimed to assess the safety of ISI in young children through a meta-analysis and to summarize the current knowledge on the effectiveness of ISI in anastomotic esophageal strictures. Methods A systematic literature search was performed in Embase, Medline, Web of Science Core Collection, Cochrane Central Register of Controlled Trials and Google Scholar up to August 16 2021. Studies focusing on ISI and involving children up to two years were included in the meta-analysis for the safety assessment. All studies evaluating the use of ISI as adjuvant treatment in anastomotic esophageal strictures in children were included in the systematic review to assess the effectiveness of the intervention. Results The literature search yielded 8253 articles. A total of 57 studies were included, of which 55 for the safety and five for the effectiveness assessment. The overall complication rate was 7%, with a greater incidence of local complications compared to systemic complications. Six studies (with a total of 367 patients) evaluated adrenocorticotropic hormone and cortisol levels, of which four reported hypothalamic-pituitary axis suppression. Two children (0.6%) received replacement therapy and all patients recovered uneventfully. A mean number of 1.67 ISI were performed per esophageal atresia (EA) patient. A reduction of needed dilatations was seen after ISI, compared to the number of dilatations performed before the intervention (5.2 vs. 1.3). Conclusion The insufficient data emphasized the need for further prospective and comparative studies. Results from this meta-analysis and systematic review address ISI as a safe and effective technique. Close clinical follow-up and growth curve evaluation are advisable in patients receiving ISI.